Strategi Kampanye Komisi Pemilihan Umum (KPU) dalam Meningkatkan Pemilih Aktif Pada Pemilu 2019 (Kajian Deskriptif di Akun Instagram KPU): THE GENERAL ELECTIONS COMMISSION (KPU) CAMPAIGN STRATEGY IN INCREASING ACTIVE VOTERS IN ELECTION 2019 (Descriptive Study on KPU Instagram Accounts) - Budifebrianto, Rian; Delliana, Santi (Restorica: Jurnal Ilmiah Ilmu Administrasi Negara dan Ilmu Komunikasi, 2020)
Communication in social media is a form of communication carried out by many parties, one of which is KPU. Welcoming the political year, the KPU is actively conducting campaigns to increase the number of active voters monitored each year. One of the campaign strategies used by KPU is using Instagram social media; according to KPU, this internet-based social media can reach the public widely and quickly. This study uses a qualitative research approach with the post-positivism paradigm. In this research, the model used is Ostergaard's campaign model. Based on research results, in conducting campaigns through Instagram, KPU utilizes several features on Instagram, such as posting, hashtags, and captions. In addition to using the Instagram feature, KPU also prioritizes speed in clarifying emerging hoaxes and attractive designs in its Instagram posts. KPU can create a positive perspective in the community, especially new voters who are expected to become active voters. KPU is a trusted distributor of information for the public regarding the 2019 elections.